MUSHAF KUNO AL-QUR`AN DI DESA PAKIS, REMBANG: Kajian Kodikologi dan Konsistensi Penggunaan Kaidah Rasm ‘Uthmāni - Dewi Nailatul Fadilah; Muhammad Asif (STAI AL-ANWAR SARANG, 2024)
This article presents a codicological analysis and consistency in the use of rasm 'uthmānī rules in ancient Quranic manuscripts found in Pakis village, Sale District, Rembang Regency. This research is qualitative with a philological approach. The philological method is used to reveal aspects of the codicology of the Mushaf, while the coherence test is based on six rules formulated by al-Suyūṭi, namely, the ḥadhf al-Ḥurūf rules, the ziyādah al-Ḥurūf rules, the al-Hamz rules, the al-Badl rules, the al-Faṣl wa al-Waṣl rules, and Mā Fīhi Qirā`atāni fa Kutiba ‘alā Iḥdahumā. Based on data testing that has been carried out, it was discovered that the studied manuscript was copied in the 19th century. This is demonstrated by the paper supports with the PROPATRIA watermark and the HIV DELDEN countermark, as well as the chainline without a shadow. The condition of the mushaf is uncovered and corrupted in several parts, so that only surah al-Māidah to surah al-Ghāshiyah remain. This manuscript does not have any illumination, but there are several symbols showing the change of juz, rukū', end of verse and name of surah. Copying Mushafs does not consistently use the rules of rasm uthmānī in terms of adding letters, subtracting letters, hamzah, replacing letters, separating and connecting letters, and writing sentences that have multiple reading variants. This was caused by the absence of references to the writing of the Quran in Indonesia at that time. Keywords: Ancient manuscripts of the Quran, philology, rasm consistency.